ROLE AND IMPORTANCE OF NEGOTIATIONS IN AN INTERNATIONAL BUSINESS ENVIRONMENT - Ivanova, Lyubov (Revista Inclusiones, 2020)
The communication process plays a major role for the business and is determined by the various aspects of the business environment. The business environment is the professional development environment. The best and most profitable formula for the good management of any company is the ability of its employees to communicate effectively with external and internal audiences - colleagues, customers and consumers. For successful foreign trade it is absolutely necessary to be fluent in one of the official languages of the country - partner, to know the rules for written communication, to study the specific national, cultural and other peculiarities of the foreign contractors. Therefore, when negotiating with representatives of companies from the domestic, as well as the international market, it would be important to pay attention to the preparation of the negotiations.